A phage parasite deploys a nicking nuclease effector to inhibit viral host replication. Issue 15 (24th January 2022) - LeGault, Kristen N; Barth, Zachary K; DePaola, Peter; Seed, Kimberley D
Abstract: PLEs (phage-inducible chromosomal island-like elements) are phage parasites integrated into the chromosome of epidemic Vibrio cholerae . In response to infection by its viral host ICP1, PLE excises, replicates and hijacks ICP1 structural components for transduction. Through an unknown mechanism, PLE prevents ICP1 from transitioning to rolling circle replication (RCR), a prerequisite for efficient packaging of the viral genome. Here, we characterize a PLE-encoded nuclease, NixI, that blocks phage development likely by nicking ICP1's genome as it transitions to RCR. NixI-dependent cleavage sites appear in ICP1's genome during infection of PLE(+) V. cholerae . Purified NixI demonstrates in vitro nuclease activity specifically for sites in ICP1's genome and we identify a motif that is necessary for NixI-mediated cleavage. Importantly, NixI is sufficient to limit ICP1 genome replication and eliminate progeny production, representing the most inhibitory PLE-encoded mechanism revealed to date. We identify distant NixI homologs in an expanded family of putative phage parasites in vibrios that lack nucleotide homology to PLEs but nonetheless share genomic synteny with PLEs. More generally, our results reveal a previously unknown mechanism deployed by phage parasites to limit packaging of their viral hosts' genome and highlight the prominent role of nuclease effectors as weapons in the arms race between antagonizing genomes. Lay Summary: Parasites of viruses, often referred to as satellites, are found in all domains of life and have been co-opted for host defense across diverse virus-host systems multiple independent times. This study describes the mechanism by which such an element prevents a bacterial virus (a 'phage') from otherwise infecting Vibrio cholera and related bacteria. The study is of broad interest to investigators with interests in phage-host interactions and microbial genetics.